Venezuelan Equine Encephalitis Virus Infection in Nonhuman Primate, Guatemala, 2023 - Wendy K. Jo; Marta Piche-Ovares; Lincoln Carranza; Carlo Fischer; Sebastian Brünink; Laura Paul; Alejandro Morales; Fernando Martinez; Jan Felix Drexler (Emerging Infectious Diseases)
We isolated Venezuelan equine encephalitis virus (VEEV) subtype IE phylogenetically related to Gulf Coast strains in a spider monkey (Ateles geoffroyi) released from a rescue center in Guatemala. Serologic testing of 118 monkeys indicated no additional VEEV infections. Infection of a primate warrants intensified surveillance of VEEV transmission cycles in North America.